2013
DOI: 10.4236/ijamsc.2013.11009
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Lanthanides, Thorium, Uranium and Plutonium in Irradiated (Th, Pu)O2 by Liquid Chromatography Using α-Hydroxyiso Butyric Acid (α-HIBA)

Abstract: An HPLC method is presented for the separation and determination of lanthanides (Lns), thorium (Th), uranium (U) and plutonium (Pu) from irradiated (Th, Pu)O 2 . Individual separation of Lns, Th, U and Pu is a challenging task because of 1) lanthanides having similar physical and chemical properties, 2) presence of complex matrix like irradiated fuel and 3) the co-existence of multiple oxidation states of Pu. Different procedures were developed for separation of individual lanthanides and actinides. The indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
1
8
0
1
Order By: Relevance
“…The data obtained were in agreement with those obtained by isotope dilution-thermal ionisation mass spectrometry [20].…”
Section: Separation Of Th U(vi) and Pu(iv)supporting
confidence: 80%
See 3 more Smart Citations
“…The data obtained were in agreement with those obtained by isotope dilution-thermal ionisation mass spectrometry [20].…”
Section: Separation Of Th U(vi) and Pu(iv)supporting
confidence: 80%
“…It is seen that baseline separation was achieved using isocratic mode when mandelic acid is employed as the eluent. It may be noted that in the previous study employing HIBA as the eluent, a gradient of both the eluent and MeOH was required to achieve the base line separation [20]. Figure 5 shows the calibration curves obtained for Th, U(VI) and Pu(IV) using aliquots taken from solutions prepared by the dilution of the synthetic mixture in the concentration range 1 ppm to 50 ppm, under the optimised conditions as shown in Figure 4.…”
Section: Separation Of Th U(vi) and Pu(iv)mentioning
confidence: 97%
See 2 more Smart Citations
“…The effect of concentration of eluent HIBA on the elution of lanthanide has been investigated and it is reported that with increase in concentration of HIBA, the number of undissociated HIBA molecules in the mobile phase increases which results in increased complexation of metal ion, thereby decreasing the retention time of metal ion in the resin phase. However, the optimum concentration for an effective separation of lanthanides is reported to be 0.25 M .…”
Section: Resultsmentioning
confidence: 99%